2003
DOI: 10.1016/s0167-6296(03)00046-8
|View full text |Cite
|
Sign up to set email alerts
|

A consistency test of the time trade-off

Abstract: This paper tests the internal consistency of time trade-off utilities. We find significant violations of consistency in the direction predicted by loss aversion. The violations disappear for higher gauge durations. We show that loss aversion can also explain that for short gauge durations time trade-off utilities exceed standard gamble utilities. Our results suggest that time trade-off measurements that use relatively short gauge durations, like the widely used EuroQol algorithm (Dolan 1997), are affected by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 32 publications
5
21
0
Order By: Relevance
“…Instead, we used a choice task to better approximate the choice-based nature of economic practice. Our results suggest that loss aversion for short durations is far less important for choice tasks than matching tasks, in accordance with other studies [9, 23]. In particular, the shortest durations ( n β  = 1,3,7) did not yield higher TTO scores than the other durations, suggesting that a choice based design causes subjects to put less emphasis on the maximization of remaining lifetime.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Instead, we used a choice task to better approximate the choice-based nature of economic practice. Our results suggest that loss aversion for short durations is far less important for choice tasks than matching tasks, in accordance with other studies [9, 23]. In particular, the shortest durations ( n β  = 1,3,7) did not yield higher TTO scores than the other durations, suggesting that a choice based design causes subjects to put less emphasis on the maximization of remaining lifetime.…”
Section: Discussionsupporting
confidence: 91%
“…The use of round numbers might encourage subjects to respond in round numbers as well, causing a proportional heuristic [10]. We chose these somewhat odd durations to make this heuristic less salient [9]. Contrary to most previous studies, we used short, intermediate, and long gauge durations, enabling a more complete test of CPTO.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may again have been caused by MET. Bleichrodt et al [9] used five different durations that were not multiples of 5, so that they were not very susceptible to a proportional heuristic. These durations were of an intermediate and long-term nature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some empirical studies found support [46], while others rejected it [7, 8], or found mixed results [9]. Given the importance of the assumption and the mixed evidence for it, more research in this area seems warranted.…”
Section: Introductionmentioning
confidence: 99%